Effects of simulated microgravity on seed germination, growth, development and accumulated secondary compounds of Hibiscus sagittifolius Kurz. cultured in vitro - Nhựt, Dương Tấn; Tuấn, Nguyễn Xuân; Anh, Nguyễn Thị Thùy; Nam, Nguyễn Bá; Huy, Nguyễn Phúc; Tùng, Hoàng Thanh; Hiền, Vũ Thị; Luận, Vũ Quốc; Vinh, Bùi Thế; Luận, Trần Công (Vietnam Journal of Biotechnology, 2018)
In the present study, Hibiscus sagittifolius Kurz. seeds were used as the plant materials for studying on the effects of simulated microgravity (on a 2D clinostat) on seed germination, shoot multiplication, growth, development and secondary metabolite accumulation. After surface sterilization, seeds were cultured on MS medium supplemeted with 30 g/l sucrose and 9 g/l agar in Petri dishes (9 seeds per dish, the seed to seed distance of 1.5 cm and kept in the same direction), and maintained in a Clinostat (2 rpm). The results showed that simulated microgravity inhibited the growth and development of Hibiscus sagittifolius roots with root length of 11.83 cm, fresh and dry weight of 58.28 and 5.23 mg, respectively but it made an increase in germination rate (87%) and accumulation of secondary metabolites (the total saponins content of 53.00 mg/g and the total coumarin content of 25.67 mg/g) after 3 weeks of culture. In addition, the simulated microgravity also resulted in positive shoot multiplication (shoot height of 3.07 cm, 6.33 nodes per shoot, 3.33 shoots per explant, and the fresh and dry weight of 401.33 and 37.00 mg, respectively), and growth and development of Hibiscus sagittifolius shoots (plant height of 12.17 cm with 5.67 leaves per shoot together with the average root length of 1.77 cm, and the fresh and dry weight of 419.00 and 36.00 mg) after 4 weeks of culture. The results from this study could be attributed to future perspectives in research on plant breeding and accumulation of secondary metabolites in medicinal plants.